Sensory profile and drivers of liking of grass-fed and total mixed ration butters - Lauren McGuinness; Mark Timlin; Sean A. Hogan; Tom F. O'Callaghan; John P. Murphy; Deirdre Hennessy; Michael O'Donovan; Ellen Fitzpatrick; Kieran McCarthy; E. Dolores O'Riordan; Andre Brodkorb; Emma L. Feeney (Food Quality and Preference, 2026)

Community engagement in the context of cancer: scoping review of definitions and measures to inform program-level analysis - Heidi J. Keeler; Regina Idoate; Brooke J. Fitzpatrick; Emma Hymel; Josiane Kabayundo; Krishtee Napit; Cynthia M. Schmidt; Shinobu Watanabe-Galloway (Cancer Causes & Control, 2025)

Population origin and heritable effects mediate road salt toxicity and thermal stress in an amphibian - Lauren M. Conner; Debora Goedert; Sarah W. Fitzpatrick; Amber Fearnley; Emma L. Gallagher; Jessica D. Peterman; Mia E. Forgione; Sophia Kokosinska; Malik Hamilton; Lydia A. Masala; Neil Merola; Hennesy Rico; et al. (Chemosphere, 2024)

Impact of feeding regimes and lactation stage on sensory attributes of Cheddar cheese - Lauren McGuinness; Mark Timlin; John P. Murphy; Deirdre Hennessy; Ellen Fitzpatrick; Kieran McCarthy; Michael O'Donovan; Tom F. O'Callaghan; Kieran N. Kilcawley; E. Dolores O'Riordan; Andre Brodkorb; Jeremiah J. Sheehan; et al. (Food Research International, 2024)

Recombinant production, characterization and industrial application testing of a novel acidic exo/endo-chitinase from Rasamsonia emersonii - Kelly Dwyer; Ian S. Bentley; David A. Fitzpatrick; Aliabbas A. Saleh; Emma Tighe; Eibhilin McGleenan; Darragh Gaffney; Gary Walsh (Extremophiles, 2023)

Disease-Relevant Single Cell Photonic Signatures Identify S100β Stem Cells and their Myogenic Progeny in Vascular Lesions - Claire Molony; Damien King; Mariana Di Luca; Michael Kitching; Abidemi Olayinka; Roya Hakimjavadi; Lourdes A. N. Julius; Emma Fitzpatrick; Yusof Gusti; Denise Burtenshaw; Killian Healy; Emma K. Finlay; et al. (Stem Cell Reviews and Reports, 2021)
A hallmark of subclinical atherosclerosis is the accumulation of vascular smooth muscle cell (SMC)-like cells leading to intimal thickening and lesion formation. While medial SMCs contribute to vascular lesions, the involvement of resident vascular stem cells (vSCs) remains unclear. We evaluated single cell photonics as a discriminator of cell phenotype in vitro before the presence of vSC within vascular lesions was assessed ex vivo using supervised machine learning and further validated using lineage tracing analysis . Using a novel lab-on-a-Disk(Load) platform, label-free single cell photonic emissions from normal and injured vessels ex vivo were interrogated and compared to freshly isolated aortic SMCs, cultured Movas SMCs, macrophages, B-cells, S100β + mVSc, bone marrow derived mesenchymal stem cells (MSC) and their respective myogenic progeny across five broadband light wavelengths (λ465 - λ670 ± 20 nm). We found that profiles were of sufficient coverage, specificity, and quality to clearly distinguish medial SMCs from different vascular beds (carotid vs aorta), discriminate normal carotid medial SMCs from lesional SMC-like cells ex vivo following flow restriction , and identify SMC differentiation of a series of multipotent stem cells following treatment with transforming growth factor beta 1 (TGF- β1), the Notch ligand Jagged1, and Sonic Hedgehog using multivariate analysis, in part, due to photonic emissions from enhanced collagen III and elastin expression. Supervised machine learning supported genetic lineage tracing analysis of S100β + vSCs and identified the presence of S100β + vSC-derived myogenic progeny within vascular lesions. We conclude disease-relevant photonic signatures may have predictive value for vascular disease. Graphical abstract

Adult vascular smooth muscle cells in culture express neural stem cell markers typical of resident multipotent vascular stem cells - Eimear Kennedy; Ciaran J. Mooney; Roya Hakimjavadi; Emma Fitzpatrick; Shaunta Guha; Laura E. Collins; Christine E. Loscher; David Morrow; Eileen M. Redmond; Paul A. Cahill (Cell and Tissue Research, 2014)

Isolation and characterization of eight polymorphic microsatellite loci for Natterer’s bat, Myotis nattereri (Vespertilionidae, Chiroptera) - David D. Scott; Seán Fitzpatrick; Deborah A. Bailie; Emma S. M. Boston; Mathieu G. Lundy; Daniel J. Buckley; Emma C. Teeling; W. Ian Montgomery; Paulo A. Prodöhl (Conservation Genetics Resources, 2013)